An Examination of the Characteristics and Interests of Undergraduate Students in Entrepreneurship - Mohd Pauzi, Nur Farahah; Mustafa, Mohd Ariff; Shamsudin, Adriana; Ahmad, Khairiah; Zazali, Ainol Sarina Ahmad; Jailani, Jalaluddin Mohamad (Advances in Social Sciences Research Journal, 2024)
The Malaysian government has developed many programmes to encourage entrepreneurial activities among university graduates, aiming to provide them with the necessary information, skills, and mindset to start successful and enduring firms. Despite these efforts, the rate of graduates involved in entrepreneurship remains low. With the rising unemployment rate in the country, worsened by the difficult economic conditions following the COVID-19 pandemic, it is crucial to promote business endeavours. This study aims to assess students’ understanding and approval of entrepreneurship-related topics in connection to their personal entrepreneurial tendencies and characteristics due to the pressing nature of the issue. 252 undergraduate students took part in the study by filling out self-administered questionnaires. The study showed a significant link between individuals’ perception of their own expertise and their willingness to embrace entrepreneurship-related matters, which in turn impacts students’ tendencies and traits associated to entrepreneurship. The pupils showed a strong inclination towards entrepreneurship, displaying characteristics such as open-mindedness, excellent cooperation, self-motivation, and a competitive spirit. These insights will help colleges develop entrepreneurship programmes to provide students with more entrepreneurial education and inspire them to pursue business opportunities.